Strategi Peningkatan Kualitas Produk Minuman Kopi Di Coffee Shop EFG Menggunakan Metode Quality Function Deployment (QFD) - Sulaeman, Dani Endrio; Wiranatha , Anak Agung Putu Agung Suryawan; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2024)
The revenue of Coffee Shop EFG xperienced fluctuations in 2023. Based on interview results, the decline in revenue was caused by a decrease in the number of customers, likely due to the presence of competing coffee shops located along the same route. The objective of this research is to determine the product quality attributes of coffee drinks that are considered important by customers, understand the level of importance and customer satisfaction, and formulate business development strategies. This research uses the Quality Function Deployment method. The analysis results indicate that there are 11 product quality attributes of coffee drinks that are considered important by customers. The highest importance value is promotion (4,59), while the highest customer satisfaction value is cleanliness (4,33). The technical parameters that need to be evaluated and improved are coffee powder brewing, coffee bean grinding, and coffee bean weighing. The recommended business development strategies include promotion enhancement, adding product variations, and conducting monthly evaluations.